The Influence of Environmental Factors on Photosynthesis - Learning Design and Assessment Plan for a STEM Curriculum - Yuxuan Liu (Eximia, 2024)
There has been a lot of attention on STEM education, but there is less STEM curriculum for teachers to have a reference point in China. The article proposes a short STEM curriculum for use by teachers in the teaching of the STEM curriculum. The curriculum is for 10th graders. Biology is the main subject integrated with mathematics and chemistry. The article shows specific course content, including 3 different experiments. Experiments in which students participate independently are more likely to sharpen their thinking. Inquiry-based learning is adopted as the educational approach, through which students can discover new causal relationships because students formulate hypotheses and test them by conducting experiments and observations. Additionally inquiry-based learning encourages students to think logically, critically, and analytically, which is helpful in increasing students’ critical thinking. Critical thinking is reasonable and reflective thinking focused on what to believe or do. Students with critical thinking skills can achieve incredible learning outcomes because they can consciously control their goals and attention. There are six dimensions of critical thinking, based on the assignment—experimental report, analysis dimension and explanation dimension will be assessed.